HISTORY AND TRANSFORMATION OF CALUNG TO PUNKLUNG - Nugroho, Yosaphat Yogi Tegar; Dukut, Ekawati Marhaenny (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2021)
Abstract: This research is carried out based on the rise of the Calung Malioboro phenomenon or Punklung, which is popularly seen at stoplight intersections. The research aims to find out the formulation of the Calung Malioboro/ Punklung history by using Maruska Svašek’s theory of Transit, Transiton and Transformation. The perspectives of Cultural Hybridity and Performing Arts Management are also applied to analyze the phenomenon. The research methodology is descriptive qualitative analysis, and the data sample used is purposive sampling. The research finds that there is a transformation process from Calung Banyumas to Calung Malioboro or Punklung, by giving attention to the local and global cultures that is evident from the Cultural Hybridity analysis done, and how the stage for the Punklung performance has been created by observing how the Performaing Arts Management has been applied in the musical groups found in each city.Key words: transformastion, calung, punklung, performing arts management, cultural hybridity